2017
DOI: 10.1097/mcg.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Morbidity and Mortality After Transjugular Intrahepatic Portosystemic Shunts

Abstract: The results of this study suggest event-free survival is similar between nonelderly and elderly patients. Although statistically significant, there is a tendency toward greater mortality and hospitalization in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Bei modernen gecoverten Stents führt das Unterschreiten einer unteren Grenze des portosystemischen Druckgradienten < 5 mm zu einem deutlich erhöhten Risiko für eine HE oder ein Leberversagen [702]. Vorhersageparameter für eine HE sind: Alter über 65 Jahre [703,704], frühere HE [673,705], Child-Pugh-Score > 10, MELD-Score > 14 [706], niedriges Serumnatrium [576] und eine Hyperbilirubinämie [698]. Neben dem MELD-Score stellte auch das Vorliegen einer Sarkopenie einen unabhängigen Risikofaktor für das Auftreten einer HE nach TIPS-Anlage dar [213].…”
Section: Kommentarunclassified
“…Bei modernen gecoverten Stents führt das Unterschreiten einer unteren Grenze des portosystemischen Druckgradienten < 5 mm zu einem deutlich erhöhten Risiko für eine HE oder ein Leberversagen [702]. Vorhersageparameter für eine HE sind: Alter über 65 Jahre [703,704], frühere HE [673,705], Child-Pugh-Score > 10, MELD-Score > 14 [706], niedriges Serumnatrium [576] und eine Hyperbilirubinämie [698]. Neben dem MELD-Score stellte auch das Vorliegen einer Sarkopenie einen unabhängigen Risikofaktor für das Auftreten einer HE nach TIPS-Anlage dar [213].…”
Section: Kommentarunclassified
“…Most studies that have specifically evaluated TIPS outcomes in older populations have defined elderly to be 60 [16] or 65 [14,15] years and older or have not reported rates of post-TIPS encephalopathy or readmission rates. These studies had total sample sizes ranging from 23-64 patients.…”
Section: Discussionmentioning
confidence: 99%
“…All three died within 30 d post TIPS despite a low baseline MELD ranging from 10-16, suggesting that age over 80 may be associated with a higher mortality than seen with patients in their seventies. [12,14,[17][18][19][20][21]27]. We had too few patients 80 years and older to study as a separate group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors attributed this finding to the age-related physiologic decline in functional hepatic reserve as well as to the increased burden of comorbidities seen in older patients. In a case-control study, Suraweera et al 28 found a trend toward greater hospitalizations and mortality in patients !65 years old.…”
Section: Advanced Agementioning
confidence: 97%